Gold-catalyzed synthesis of N,O-heterocycles - Hashmi, A. Stephen K. (Pure and applied chemistry, 2010)
The selective synthesis of oxazoles, alkylidene oxazoles, and 1,3-oxazines from N -propargyl carboxamides by choosing gold(III) or gold(I) catalysts and selecting terminal or internal alkynes as substrates is discussed. The mechanistic studies based on labeling experiments and intensive in situ NMR studies indicate an anti -oxyauration step and a proto-deauration with retention of the sterical arrangement at the double bond. The synthetic scope for gold(I) catalysts is very broad, allowing selective conversions to products with properties of chelate ligands, reactions of bromoarenes and the formation of acceptor-substituted oxazoles. With N -heterocyclic carbene (NHC) ligands in the presence of a base, even the vinylgold intermediates of the reactions leading to 1,3-oxazines could be isolated, a reaction with a great potential for future mechanistic studies and future applications of gold catalysis.